Development of an Annual Program Evaluation Tool for Residencies (PET-R) - Erin Dehon; Natalie Gaughf; David Fowler (Association of American Medical Colleges, 2015)
Abstract As part of the Next Accreditation System, ACGME-accredited programs are required to conduct an annual evaluation of their quality. The ACGME requires residency programs to form a program evaluation committee (PEC); its members are responsible for conducting the annual evaluation of the residency program. As part of this process, it is required that residents be given an opportunity to provide written confidential feedback about their residency program. The Program Evaluation Tool for Residencies (PET-R) was developed to both meet the new ACGME requirements and guide program improvement efforts. The PET-R is a web-based residency program evaluation survey intended to be completed by residents on an annual basis. It allows residents to provide programmatic feedback confidentially. The purpose of the PET-R is to provide departmental leadership and the PEC with valuable feedback from the perspective of the residents that can be used to improve the residency program. The measure was developed to evaluate the fundamental aspects of a residency program, including the following: program director, assistant program director(s), chair of the department, program coordinator, faculty, training, research, didactics, strengths and weaknesses of the residency program, and recommendations for program improvement. To our knowledge, the PET-R represents the first program evaluation tool that is available for use. The results of the PET-R are helpful in identifying the strengths and weaknesses of a residency program, which can, in turn, facilitate program improvement efforts.